2012
DOI: 10.1177/1352458512458010
|View full text |Cite
|
Sign up to set email alerts
|

CSF neurofilament and N-acetylaspartate related brain changes in clinically isolated syndrome

Abstract: Background:Axonal damage is considered a major cause of disability in multiple sclerosis (MS) and may start early in the disease. Specific biomarkers for this process are of great interest.Objective:To study if cerebrospinal fluid (CSF) biomarkers for axonal damage reflect and predict disease progression already in the earliest stages of the disease, that is, in clinically isolated syndrome (CIS).Methods:We assessed CSF levels of neurofilament heavy (NFH), neurofilament light (NFL) and N-acetylaspartate (NAA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 36 publications
5
70
2
5
Order By: Relevance
“…If present, such a relationship would require age dependent cut-off values [7]. A major limitation to all studies in this field to date [6,7,11,3234] is that they have not been powered to investigate this potential correlation in the CSF, due to lack of samples from a sufficiently large healthy control group across all age categories. Again, the availability of the present method to investigate this in readily available serum samples is highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…If present, such a relationship would require age dependent cut-off values [7]. A major limitation to all studies in this field to date [6,7,11,3234] is that they have not been powered to investigate this potential correlation in the CSF, due to lack of samples from a sufficiently large healthy control group across all age categories. Again, the availability of the present method to investigate this in readily available serum samples is highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum NfL and Nf heavy chain levels have been found in neurological conditions other than MS, such as amyotrophic lateral sclerosis and Guillain-Barré syndrome, and have also been used as a marker of neurotoxicity after chemotherapy 5 6 10 11. Results from previous studies in CIS have been controversial with one study showing slightly higher CSF NfL levels in patients with CIS converting to CDMS than in NC,4 while other studies have not 12 13. It should be noted that even in this cohort, serum NfL levels were to some extent higher in FC than NC and it is plausible that by increasing the sample size the difference may become statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies have suggested a relationship between cognitive dysfunction and MRI measure of axonal damage in MS. 12 However, this is the first study evaluating the relationship between cognitive processing and CSF NFL levels at the earliest stages of MS. Since NFL concentration in MS increases both in acute and in chronic axonal damage, 8,27 the possibility that the observed NFL changes are related to acute axonal dysfunction must be taken into account. In order to minimize this possibility, we included patients far from clinical exacerbation.…”
Section: Discussionmentioning
confidence: 99%